Failure Mode and Effect Analysis –A Quantitative Technique for Improving Quality of Teaching and Training in B-Schools (International Journal of Scientific Research and Management (IJSRM), 2015)
The products and services are developed now-a-days by following the specification developed by R&D wings. The R&D wings consider all possible design aspects specifically targeting the performance of the products. The design specifications consider the functions of the product in the normal condition. The scenario is equally important when we consider the case of services, where the service delivery processes need to meet all the needs of the users group. The services like hospitals, fuel pump, hotels and educational institutes need to carefully design their services process so as to gain complete satisfaction level of the customers. The very design aspects of the services need to incorporate the possible zone of failures and its effect on the service process. This ensures better preventive mechanism for the service process. The current study has considered the scenario of teaching B-Schools courses and its probable failure mode and effects. The quantitative techniques FMEA (Failure Mode and Effect Analysis) is carried out and also ANOVA is used to understand the failure zones and their implications in teaching.